Optimization of Effective Parameters on Biohydrogen Production Using Bioaugmentation - Saeed Khesareh; Seyed-Ahmad Ataei (Biomechanism and Bioenergy Research)
Biohydrogen production is a green method that utilizes organic materials in activated sludge as a substrate. The process involves microorganisms contracting the volume of the sludge content to produce hydrogen, CO2, CH4, and etc. However, the efficiency of this process is low. In this study, bioaugmentation was carried out by inoculating a 10% Escherichia coli suspension adapted in whey and activated sludge medium. The effects of parameters such as pH, temperature, and stirring, the concentration of whey as carbon source and nitrate as nitrogen source on hydrogen production were screened using the Plackett-Burman method with Minitab 21 software. Among the selected parameters, pH, temperature, concentration of whey and nitrate were found to be the most effective parameters in hydrogen production and were further optimized using Response surface methodology. Stirring wasn’t statistically significant. The optimum conditions for hydrogen production were pH=5.4, temperature=39 ˚C, whey concentration=30 g/L, and nitrate concentration=3.6 g/L. Under these conditions with a 10% inoculation, the total volume of gas production was extended to 1.61 L per liters of activated sludge with 0.046 mole H2 per liters of activated sludge. Comparing the bioaugmentation method with other method showed that the total time of the process decreased by 8 hours. Additionally, hydrogen production started after 10 hours of incubation and reached its maximum value in 16 hours, resulting in a 59% increase in productivity in less than 16 hours.